When do Ophthalmology Residents Study to Prepare for The National Exam? - Widyandana, Doni; Widyaputri, Felicia; Sasongko, Muhammad Bayu; Supanji, Supanji; Alam, Irmastuti Lukitaning (Universitas Gadjah Mada, 2024)
Background: Ophthalmology residents are occupied with clinical services in the hospital. They only have limited time to study. Since 2022, we established a progress test for a residents to facilitate their study especially during the national examination preparation that is obligated to be completed once per year.Aims: To report the allocated time for completing the progress test by ophthalmology residents to inform educational centres about the recommended study time for residents.Case Discussion: Data from the online progress test that was available from the Gadjah Mada e-Learning (GAMEL) platform was extracted ana analysed. The test was concisted of 60 multiple questions and opened for two weeks with a 24 hour access time. In this study, the scores, the time of the test, and time spent to complete the test were descriptively and quantitatively analysed.Results: Overall, 42 out of 55 (76.4%) and 42 out of 56 (75.0%) residents completed the progress test with a total test attempt of 60 and 51 times in 2022 and 2023, respectively. The mean score achieved was 43.3 (min-max 3.3-70.0). Majority of residents (65.8%) access the test at between 16.00 - 23.00 Western Indonesian Time (WIT), while 19.8% and 14.4% at between 09.00 - 16.00 and 03.00 - 09.00 WIT. The mean time spent to complete the test was 55.2 +- 20.9 minutes.Conclusion: Most ophthalmology residents spent their time for completing the progress test after working hours with an average duration of less than an hour. Any national exam preparation programs can be scheduled in this time for better resident’s engagements.